Educação geográfica: concepções e desafios de professoras(es) de geografia da rede estadual de educação de Francisco Beltrão-Pr - Figueiredo Junior, Jalme Santana de (2019)
We conducted a qualitative research as case study, together with professionals working with the teaching of Geography, in Basic Education of the state colleges located in the municipality of Francisco Beltrão-PR. Considering aspects around the theme: conceptions and challenges for a Critical and Transformative Geographic Education, we analyzed national and international educational guidelines from the 1990s (consolidation of Neoliberal policies), Brazilian legislations, bibliographical works and researches seeking to understand the spatiality of Education Geography in public schools. In fact, trying to deepen the subject, we aim to understand how concepts of Geographic Education were given and the main challenges to produce it, starting from the readings of teachers and teachers effective in the state schools of Francisco Beltrão-PR. For that, we used questionnaires and interviews. The main axes that emerged from the analyzes made revealed guiding conceptions about historical and dialectical materialism, phenomenology and historical environmental perspective. As challenges, structural issues were pointed out, such as lack of resources and excessive bureaucratic work; absence of collective planning, due to excess of students, classes and school units by each professional. In this way, we can glimpse aspects of the complex networks of influences acting in the production of the teaching of Geography in the public schools of Francisco Beltrão-PR, as well as the resistance effort of the professionals who look for a Geographic Education as a critical and transforming possibility.